A Model to Support Decision Making in the Idea Management Domain - Sérgio, Marina Carradore (2015)
Taking into account the global competitiveness, innovation has become a challenge for organizations. Idea management is an integral part of the innovation process and it is presented as an essential factor for achieving success. Due to the volume and sudden peaks in submissions of ideas, the appropriate analysis and the allocation of resources for investment are important issues to be addressed. The objective of this paper is to present a model for the management of ideas based on ontology and cluster analysis in order to maximize resources for investment in ideas. So as to demonstrate the model feasibility it was prepared a dataset comprised of fifty-five ideas collected from the Starbucks® site. These ideas were then stored in the domain ontology and were used as subsidies for the cluster analysis and for the building of a knowledge base. As a result, it was identified groups with similar ideas that, when analyzed, foster a greater potential for observation and may indicate patterns and trends that can assist in decision making.